36.4k views
0 votes
2x - 2(4x-3) = 6 - 6x​

1 Answer

4 votes

Answer:

x=

Explanation:

Open parenthesis first:

2x-8x+6=6-6x

Combine like terms:

-6x+6=6-6x

Then move all like terms to one side:

6-6=-6x+6x

Simplify:

0=0

0=0 is true, so x can equal any number and the result will be true. (Like the number 4, for example. If x was 4, you would get 4=4.)

~Stay golden~ :)

User Archana
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.